APLIKASI E-COMMERCE DISTRO MAHODENK PANGKALAN BUN (Information Technology and Telematics, 2014)
Abstract - Mahodenk Distro is a business selling clothes, especially teenagers. However, the current business processes run by Distro Mahodenk still manual. Buyers should look at its own catalog is in residence sellers and the information provided is also only through word of mouth or use existing social networks. An E-commerce will help existing businesses, because the items offered can be accessed by anyone, anytime and anywhere. By considering the various problems that exist and the many benefits and advantages are achieved by E-commerce. Keywords – Ecommerce, Mahodenk, Base Bun